Simulation Study On Non-Homogenous System Of Non-Invasive Ert Using Comsol Multiphysics - Yasmin, Abdul Wahab; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Leow, Pei Ling; Suzanna, Ridzuan Aw; Fazlul Rahman, Mohd Yunus; Herlina, Abdul Rahim; Naizatul Shima, Mohd Fadzil; Mohd Zikrillah, Zawahir; Juliza, Jamaludin; Muhammad Saiful Badri, Mansor; Mohd Fadzli, Abdul Sahib; et al. (Penerbit Universiti Teknologi Malaysia, 2015)
The non-invasive sensing technique is one of the favourite sensing techniques applied in the process tomography because it has not a direct contact with the medium of interest. The objective of this paper is to analyse the simulation of the non-homogenous system of the non-invasive ERT using finite element software; COMSOL Multiphysics. In this simulation, the liquid-air medium is chosen as the non-homogenous system. A different analysis of the non-homogenous system in term of the different position of the single air, different size of the single air and the multiple air inside the vessel were investigated in this paper. As a result, the location, size and multiple air inside the pipe will influence the output of the non-invasive ERT system. A liquid-gas medium of non-homogenous ERT system will have a good response if the air is located near the source, the size of the air is large enough and it has multiple air locations inside the pipe.